Moderate influenza vaccine effectiveness against influenza A(H1N1)pdm09 virus and low effectiveness against A(H3N2) virus among older adults during 2013-2014 influenza season in Beijing, China - Li Zhang; Yang Pan; Chunna Ma; Wei Duan; Ying Sun; Shuangsheng Wu; Man Zhang; Yi Tian; Yang Zheng; Peng Yang; Quanyi Wang (Taylor & Francis Group, 2018)
Background: Since 2007, trivalent inactivated influenza vaccine has been provided free-of-charge to older adults aged ≥60 years in Beijing, China, but the data regarding influenza vaccine effectiveness (VE) among these people are very limited so far. We sought to estimate influenza VE against medically-attended laboratory-confirmed influenza illness among older adults during the 2013-2014 season. Methods: The influenza-like illness (ILI) patients aged 60 years and older who participated in the influenza virological surveillance of Beijing during 2013-2014 influenza season were recruited in this study. A test-negative design was employed to estimate influenza VE among older adults by using logistic regression models. VE was estimated using logistic regression, adjusted for sex, age, interval (days) between illness onset and specimen collection, and week of illness onset. Results: Between 1 November, 2013 and 30 April, 2014, a total of 487 elderly ILI patients were enrolled in the study, including 133 influenza-positive cases (of whom 6.8% were vaccinated) and 354 influenza-negative controls (of whom 10.2% were vaccinated). Among 133 influenza-positive cases, 51 tested positive for A(H1N1)pdm09 virus, 22 positive for A(H3N2) virus, 52 tested positive for B/Yamagata-lineage virus, 2 positive for B/Victoria-lineage virus, 1 positive for both A(H1N1)pdm09 and A(H3N2) viruses, and 5 tested positive for viruses of unknown subtype or lineage. The adjusted overall VE was estimated as 32% (95% CI:-48-69), with 59% (95% CI: −79-90) against A(H1N1)pdm09, 22% (95% CI: −253-83) against A(H3N2) and −20% (95% CI: −239-58) against B/Yamagata-lineage viruses. Conclusions: These results suggested a modest protective effect of the 2013-2014 influenza vaccine among older adults in Beijing which was not statistically significant, with higher VE against the A(H1N1)pdm09 viruses compared to A(H3N2) and B viruses.